The Effect of Previous Languages on Pausing Patterns of Iranian EFL Learners - Banitalebi, Zahra (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
This study aimed to investigate the effect of pausing patterns of previously learned languages on the pausing patterns of a foreign language. So, it compared the pausing patterns of monolingual (Persian speakers) and bilingual (Iranian Turkish speakers; L1: Turkish and L2: Persian) EFL learners. To this end, via an Oxford Placement test, a sample of 40 male and female advanced learners was selected. Three reading passages were used to measure students’ fluency in terms of their pausing patterns in the prepared mode of speech. The speeches were recorded and analyzed by Praat Software. The results showed a lack of a strong relationship either with regard to pause frequency or pause duration across the three languages, suggesting important implications for Threshold and Linguistic Interdependence hypotheses.